DESAIN PLTS ATAP KAMPUS UNIVERSITAS UDAYANA: GEDUNG REKTORAT - Maruli Pangaribuan, Bagas; Dwi Giriantari, Ida Ayu; Sukerayasa, I Wayan (Jurnal SPEKTRUM; Vol 7 No 2 (2020): Jurnal SPEKTRUMDO - 10.24843/SPEKTRUM.2020.v07.i02.p12, 2020)
Utilization of renewable energy is a solution to overcome electricity demand, including PV. PV rooftop can be applied in every building, where solar modules can be placed on the roof buildings. It also can be done in the University of Udayana Rectorate building because the roof has the potential of PV and capable of being a power supply to meet its own needs. This study will discuss about the design PV rooftop of the Udayana rectorate building. It simulates the helioscope with an optimal angle of 14.660 get the result with solar module as much as 135 units with 2 inverter pieces of 50 kW the capacity of 45.2 kWp PLTS. While with a sloped roof angle of 15.60 get the solar module result as many as 137 units with 2 inverter pieces of 50 kW with PLTS capacity of 45.9 kWp. The calculating production of electric energy produced by PV by simulating HOMER get the result of PV configuration with Grid capable of supplying electrical energy of 304,772 kWh/year, where PV is able to supply at 61,217 kWh/year and Grid supplying electricity energy of 243,555 kWh/year. The results of the design PV rooftop and calculation results of electrical energy production can analyze the economy of the simulation results HOMER with the cost of selling electricity energy PV to PLN in the amount of Rp. 883/kWh can be said to be worthy designed because it is able to restore the cost of early investment costs PV rooftop of the rectorate building.